Pengaruh Kualitas dan Harga Terhadap Keputusan Pembelian Mobil Hybrid di Jawa Barat dengan Promosi Sebagai Variabel Intervening - Qolbi, Ridwan; Hartelina, Hartelina; Hersona, Sonny (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine and analyze the effect of product quality on hybrid car purchasing decisions in West Java. To determine and analyze the effect of price on hybrid car purchasing decisions in West Java. To determine and analyze the effect of promotion on hybrid car purchasing decisions in West Java. To determine and analyze the effect of product quality on purchasing decisions through hybrid car promotions in West Java. To determine and analyze the effect of price on purchasing decisions through hybrid car promotions in West Java. This research method uses quantitative samples used in this study as many as 100 respondents using the purposive sampling technique method, the data analysis technique used in this study is path analysis with the structural model analysis tool used in this study, namely SmartPLS. The results of the research that has been conducted can be concluded that the product quality variable has a significant effect on the promotion of hybrid cars in West Java. The price variable has a significant effect on the promotion of hybrid cars in West Java. The product quality variable has a significant effect on the decision to purchase hybrid cars in West Java. The price variable has a significant effect on the decision to purchase hybrid cars in West Java. The promotion variable has a significant effect on the decision to purchase hybrid cars in West Java. The product quality variable has a significant effect on the decision to purchase through the promotion of hybrid cars in West Java. The price variable has a significant effect on the decision to purchase through the promotion of hybrid cars in West Java.